Nonlinear Stiffness of Semi-Fixed Dowel Joints in Semi-Integral Bridges - Zhen Xu; Baochun Chen; Fuyun Huang; Yizhou Zhuang; Xiaoye Luo; Feiting Shi (Applied Sciences, 2022)
The semi-fixed dowel joint studied in this paper consists of a steel dowel with rubber sleeves and a rubber pad to connect the superstructure and the substructure and to support the main beam. This type of joint is suitably used in retrofitting a jointed bridge with high-stiffness substructure into a semi-integral bridge. This study aimed to investigate the nonlinear stiffness of the joint, which is the key parameter in the retrofitting design. Taking the real joint in a retrofitted semi-integral bridge as a prototype, tests on full-scale models were carried out, in which the wall thickness of the rubber sleeve and the thickness of the rubber pad were taken as parameters. The test results show that the wall thickness of the rubber sleeve is the main factor affecting the radial stiffness and the flexural stiffness of the semi-fixed dowel joint. With the decrease of the wall thickness of the rubber sleeve, the radial stiffness decreases while the flexural stiffness increases. However, the thickness of the rubber pad has little influence on both the radial and flexural stiffness of the joint, and its main role is only vertical loading-bearing. If the longitudinal deformation of the main beam of a bridge under maximum temperature variation is 10 mm as the allowance value of engineering design, the wall thickness of the rubber sleeve for this joint should not be less than 40 mm. At last, on the basis of experimental research and theoretical analysis, the formulas of radial stiffness and flexural stiffness are fitted; it can be used as reference for practical engineering application, or for formulation of relevant specifications.